Three widely separated positions in the 16S RNA lie in or close to the ribosomal decoding region; a site-directed cross-linking study with mRNA analogues. - Dontsova, O (1992)
Synthetic mRNA analogues were prepared by T7 transcription, each containing several thio-uridine residues at selected positions. After binding to the ribosome in the presence of cognate tRNA, the thio-U residues were activated by UV irradiation and the resulting sites of cross-linking to 16S RNA analysed. Three distinct cross-links were consistently observed: (i) from position '+6' of the mRNA (the 3'-base of the A-site codon) to base 1052 of 16S RNA; (ii) from position '+7' of the mRNA to base 1395; and (iii) from '+11' to base 532. Individual yields of the cross-links were strongly dependent on the particular mRNA sequence in each case. The '+11/532' and '+6/1052' cross-links were always entirely tRNA-dependent, whereas the '+7/1395' cross-link was observed at lower intensity in the absence of tRNA. In the presence of a second (A-site bound) tRNA the +6/1052 cross-link was markedly reduced. A cross-link to the 1050 region was again observed when a message carrying a thio-U at position '+9' was translocated on the ribosome so as to bring the thio-U to position +6. Taken together, the data are incompatible with some current models both for the three-dimensional arrangement of 16S RNA and for the orientation of the tRNA-mRNA complex in the ribosome.